Indonesian adaptation and psychometric properties evaluation of the Mental Help-Seeking Intention Scale (MHSIS) - Syakarofath, Nandy Agustin; Widyasari, Dian Caesaria (Jurnal Ilmiah Psikologi Terapan, 2026)
Mental health has become a global concern due to its substantial impact on individual functioning and well-being. Therefore, the availability of valid and reliable instruments to assess intentions to seek formal mental health help is essential. This study aimed to adapt the Mental Health Seeking Intention Scale (MHSIS) into Indonesian and to examine its psychometric properties among adolescents. Participants were 1,366 adolescents aged 16–18 years in East Java, recruited using convenience sampling. The study was conducted in two stages: instrument adaptation through translation and expert judgment to assess content validity, followed by psychometric evaluation. Content validity was supported by expert ratings using Aiken’s V. Construct validity was examined through confirmatory factor analysis, evaluating standardized factor loadings, complemented by convergent and divergent validity analyses. Internal consistency reliability was assessed using Cronbach’s alpha. The results showed that all items demonstrated strong, significant factor loadings, and the scale exhibited excellent internal consistency (α = 0.937). Overall, these findings indicate that the Indonesianversion of the MHSIS is a reliable instrument with adequate validity evidence for measuring formal mental health help-seeking intentions among Indonesian adolescents.